Indoor, outdoor, and night work and blood concentrations of vitamin D and parathyroid hormone - Daugaard, Stine; Garde, Anne Helene; Hansen, Åse Marie; Vistisen, Helene Tilma; Rejnmark, Lars; Kolstad, Henrik A (Scandinavian Journal of Work, Environment & Health, 2018)
' ' OBJECTIVES ': 'The aim of this study was to examine blood concentrations of 25-hydroxyvitamin D (25OHD) and parathyroid hormone (PTH) among indoor, outdoor, permanent and rotating night workers and the association with hours spent outdoors on and off work days. ' ' METHODS ': 'Blood samples were collected from 425 workers (162 indoor, 112 outdoor, 118 rotating night and 33 permanent night workers) throughout all seasons. Serum concentrations of 25-hydroxyvitamin D (25OHD) and parathyroid hormone (PTH) were analyzed by isotope dilution liquid chromatography-tandem mass spectrometry (LC MS/MS) and an automated immune analyzer, respectively. Personal light exposure levels were continuously recorded and used to estimate hours spent outdoors (all workers). ' ' RESULTS ': 'Permanent night workers had 25.3% (95% CI 11.9–36.6) lower 25OHD concentration, 4.55 (95% CI 1.39–14.94) higher odds of vitamin D insufficiency (<50 nmol/L) and 14.5% [95% confidence interval (CI) 0.1–31.1] higher PTH concentration than indoor workers. Outdoor workers had similar 25OHD concentrations but 7.5% (95% CI -0.5–14.9) lower PTH concentration compared to indoor workers. Rotating night workers 25OHD and PTH concentrations did not differ from indoor workers. Concentration of 25OHD increased by 5.2% (95% CI 1.1–9.5) per hour spent outdoor at workdays in the summer. ' ' CONCLUSION ': 'Clinicians should be aware that vitamin D insufficiency may be more prevalent among permanent night workers and human resources should consider the positive effect of allowing workers to spend time outdoor during work hours.
Keywords: blood concentration; cross-sectional study; diet; indoor work; night work; occupation; occupational health; outdoor work; parathyroid hormone; risk factor; season; shift work; ultraviolet radiation; vitamin D